Application of polyjet technology in additive manufacturing of personalised nail art - Lu, Zhen (2016)
Nail art market is growing worldwide and consumers are looking for more complicated and detailed nail art designs. In this present work, commercial and non-toxic nail art has been successfully manufactured in full colours by using PolyJet rigid opaque materials via PolyJet Objet 500 Connex 3 machine. Liquid-based additive manufacturing was found to be preferable to build hollow or complex-shaped parts with thin walls. In this paper, 2 sets of nail art were designed, manufactured out and evaluated. The results showed that PolyJet can help to enhance the productivity and efficiency of the nail art making process compared with traditional method. The results also suggested that PolyJet technology may bring potential profits and cost savings to the company and nail art industry by technological innovation.